RTE Act 2009: Power or Plight for a Parent? - SHARMA, ANJALI; RAWAT, NEHA (THE PRIMARY TEACHER, 2025)
The paper is themed on the fact that RTE Act2009 came into force with a hope of change for parents as well as children. The main discussion point is that, whether the children have actually got benefitted by it and parents have got the long-awaited breath of relief or not. Another focus point is, will this Act shorten the gap between underprivileged and middle class family children by bringing equal educational opportunities for all. From the following discussion, it can be stated ostensibly enough that RTE’s implementation has further broadened the gap between two economic strata, leaving parents of both the groups wondering how RTE has changed the educational scenario. Finally the paper suggests that to gain its aspired results the government should take some steps like common school system in which all the groups can come onto one platform. It should also aim to create widespread awareness among parents about RTE Act to make them realize the power instead of plight of RTE